The Potential Bone Regenerative Effects of DFDBA, Simvastatin and Platelet Rich Fibrin, Radiographically and Histologically of Intra-Bony Periodontal Defects in White New Zealand Rabbits - El-dien, Asma M. Sarag; Fathy, Shereen; El-din, Yasmine Alaa (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: This study aimed to evaluate and to compare the regenerative power of simvastatin, Demineralized Freeze-Dried Bone Allograft (DFDBA) allograft, platelets rich Fibrin (PRF), and a combination of these materials radiographically and histologically in the intra-bony periodontal defects in white New Zealand rabbits. MATERIALS AND METHODS: This study was conducted on 54 defects in 27 adult male rabbits (n = 27) which were divided into three groups according to the follow-up preplanned scheduled for 1, 2, and 3 weeks. The selected materials were induced as following: A=DFDBA, B=Simvastatin, C= PRF, D=A+C, E=B+C, and F=negative (control group). The intra-bony periodontal defects were induced as the form of one osseous wall defect of 10 mm height, 4 mm depth between the first and the second molars. Then, samples were prepared for histological evaluation. Radiographic assessment was done using computed tomography radiography which was carried at different time intervals as the following baseline, 1, 2, and 3 weeks later. Statistical analysis was performed using ANOVA. RESULTS: After evaluating the results, macroanatomy, radiographically, and histologically, it is thus confirmed that DFDBA allograft combined with PRF create the best bone regenerative results, followed by DFDBA, Simvastatin, simvastatin+ PRF, control group, and finally PRF. CONCLUSION: All of the materials examined in this study showed different percentage in terms of bone density and bone regenerative effects. However, the best results for bone density of the DFDBA + PRF group were recorded after 3 weeks. Thus, the study concludes that a combination of DFDBA + PRF reflects the best properties of both materials in terms of bone density results of the defect. Such results are particularly significant for the selection of bone regeneration materials, and generally, for periodontal regeneration.